REVIEW: K. Biginas, S. Sindakis, A. Koumproglou, V. Sarantinos & P. Wyer (Edited by), Small business management and control of the uncertain external environment, Advanced Strategies in Entrepreneurship, Education and Ecology, Emerald Publishing, 2022. - Palazzi, Federica (Piccola Impresa / Small Business, 2023)
The book faces the topic of uncertainty that affects the economy. The social unrest, the pandemic, and the effects of climate change are features of this time when small businesses must operate. But how can small companies react and control external factors? It is the question that authors try to answer. This book distinguishes itself with a multidisciplinary approach, combining research and practitioner perspectives.